Isolated ischaemic lesions in the foot motor area mimic peripheral lower-limb palsy - Alonso, Angelika; Gass, Achim; Griebe, Martin; Kern, Rolf; Roßmanith, Christina; Hennerici, Michael G.; Szabo, Kristina (Journal of neurology, neurosurgery, and psychiatry, 2010)
Isolated monoparesis is an uncommon symptom of acute ischaemic stroke, and in some cases the lack of additional clinical signs may make it difficult to decide on its peripheral or central origin. Acute ischaemic distal arm paresis presenting with radial- and ulnar-like distribution has been shown to be caused by small cortical lesions in the motor hand cortex.1 Similarly, monoparesis of the lower limb with peripheral-like appearance can in rare cases occur as a feature of cerebral ischaemia. We report six patients with acute ischaemic distal lower- limb paresis. - - Six patients with acute distal lower-limb paresis underwent cranial MR imaging using a standardised stroke protocol including T1-, T2-, diffusion-weighted images (DWI) and MR angiography (MRA) within 24 h after symptom onset. A detailed neurological examination was performed daily, and motor-evoked potentials were recorded in all patients. Additionally, all patients underwent further routine investigations including extra- and intracranial Doppler-/duplexsonography, 24 h electrocardiography and echocardiography. - - All patients presented with acute onset of painless and isolated distal lower-limb paresis. Three patients showed a peroneal distribution of palsy …
Gesehen am 12.03.2021